Herding behaviour in Bangladesh stock market : a case of Dhaka stock exchange - Saha, Sangit (2019)
The paper attempts to investigate the presence of herding behaviour in Dhaka stock exchange (DSE), the prime bourse of Bangladesh stock market. In this study, the models proposed by Christie and Huang (1995) and Chang et al. (2000) have been applied to detect market wide herding. Both daily and monthly data for the period of January 2005 to December 2018 are used. The results show that the investors of Dhaka stock Exchange are involved in herding activity. More specifically, this study finds evidence of herding for the whole study period (2005-2018), bullish and bearish market, first sub-period (2005 to 2011) and for the stock market crash period (2010-2011). Herding is detected only with the non-linear model of Chang et al. (2000) for daily data. However, the result fails to find evidence of herding for the second sub-period (2012 -2018). In this paper, the result of previous study conducted by Ahsan and Sarkar (2013) on herding behaviour in DSE has also been compared. The finding of this study is inconsistent with the finding of their study since they fail to detect herding by applying similar methodologies. The probable reason for finding different result in the previous study is using different market portfolio DSI (DSE all share price index) which includes both liquid and illiquid stocks. On the other hand, the index (DS30) used in this study includes only active and most liquid stocks. Moreover, in this study, a probable reason for detecting herding for the crash period is considering longer time frame for the crash period comparing to the previous study. The result is important for million of small investors of the market to avoid the psychological trap or irrational behaviour involved with investment decisions.